1975
DOI: 10.1021/bi00673a030
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic properties of substrate-attached glycoproteins from normal and virus-transformed cells

Abstract: Balb/c 3T3, SV40-transformed 3T3 (SVT2), and Con A revertant variants of transformed cells leave a layer of glycoprotein on the culture substrate upon EGTA mediated removal of cells. The metabolic properties of this substrate-attached material (glycoprotein) have been examined. Pulse and cumulative radiolabeling experiments with glucosamine and leucine precursors established that this substrate-attached material accumulates on the substrate in growing cultures until cells have completely covered the substrate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Fibronectin shows a similarly restricted distribution when visualized by indirect immunofluorescence (see below). Furthermore, deposition of radiolabeled SAM onto the substratum ceases when the cells have completely covered the substratum, although the amount of radiolabeled macromolecular material shed into the medium continues to increase [19]. At least some of this material should have access t o the substratum, since antibody is able to penetrate under the cells (see below).…”
Section: Sam Represents Cell-substratum Adhesion Sitesmentioning
confidence: 99%
“…Fibronectin shows a similarly restricted distribution when visualized by indirect immunofluorescence (see below). Furthermore, deposition of radiolabeled SAM onto the substratum ceases when the cells have completely covered the substratum, although the amount of radiolabeled macromolecular material shed into the medium continues to increase [19]. At least some of this material should have access t o the substratum, since antibody is able to penetrate under the cells (see below).…”
Section: Sam Represents Cell-substratum Adhesion Sitesmentioning
confidence: 99%
“…He proposed that the dif ference between cells requiring or not requir ing serum for spreading might depend upon whether the cells were able to produce an ap propriate spreading factor (o coat the sub strata. since Culp et al [1975] had described a glycoprotein which was secreted by a fibro blast cell-line and adsorbed to the sub stratum. In his review, Grinnell [1978] consi dered the role of microexudates and con ditioned medium in cell adhesion.…”
Section: Cell Attachment To the Substratummentioning
confidence: 99%
“…A variety of experimental approaches have now been used in our laboratory to indicate that most of the components in SAM may be direct participants in the cell-substrate adhesion process, although definitive proof for their precise molecular role is still lacking. Pulse-chase analysis of the metabolic source of SAM (8) and autoradiography experiments to determine its topographical relationship with regard to the location and movement of cells on the substrate (9) indicated that SAM had not resulted from secretion of components into the medium followed by nonspecific binding to the substrate, but that SAM was some portion of the cellular "footpads" on the underside surface by which the cell adheres to the substrate (10, 11).…”
Section: Cell Removalmentioning
confidence: 99%
“…"Footpads" (10,11,28) are localized blebs of surface membrane on the underside surface of the cell by which it adheres to the substrate, and whose distribution on the substrate is similar to that of glucosamine-or leucine-radiolabeled SAM detected autoradiographically (9). ality between increased cell growth and increased accumulation of SAM (either glucosamine-or leucine-radiolabeled) until the substrate surface was completely covered with cells (8). At that point, SAM accumulation discontinued, even though transformed cells continued to grow and pile into dense layers.…”
Section: Sam Membranementioning
confidence: 99%
See 1 more Smart Citation